Circulating tumor DNA as a marker of residual tumor in colon cancer - M. Yu. Fedyanin; Kh. Kh.-M. Elsnukaeva; V. A. Aliev; T. S. Ayrapetyan; A. V. Polyakov; E. V. Moroz; V. A. Uymanov; U. A. Boyarskikh; A. A. Kechin; M. L. Filipenko; S. А. Tjulandin (Тазовая хирургия и онкология, 2018)
Colon cancer is the 3rd most common malignant neoplasm and the 4th leading cause of mortality from them. The majority of patients are diagnosed at stages II–IV, which indicates the need for markers that can predict disease progression, especially after surgical treatment. Recently, there has been a growing interest in exploring circulating tumor DNA as a marker of residual tumor in colon cancer. In 2018, the N.N. Blokhin National Medical Research Center of Oncology together with the Institute of Chemical Biology and Fundamental Medicine under the coordination of the Center for Strategic Planning and Management of Biomedical Health Risks initiated a research project entitled “Development of an assay for the diagnosis of various malignant tumors and treatment efficacy monitoring based on the analysis of circulating tumor DNA from patient blood”. This article provides a theoretical background for the project and a report on its progress made so far.